An environmental friendly animal waste disposal process with ammonia recovery and energy production: Experimental study and economic analysis. (October 2017) - Shen, Ye; Tan, Michelle Ting Ting; Chong, Clive; Xiao, Wende; Wang, Chi-Hwa
Highlights: An environmental friendly animal manure waste treatment scheme was proposed. Ammonia was removed and recovered from manure waste in the form of struvite. Horse manure waste gasification was successfully conducted in a 10 kW gasifier. Gasifier produces comparable or higher heating value of syngas as other feedstocks. The proposed scheme is financially superior to pure gasification and incineration. Abstract: Animal manure waste is considered as an environmental challenge especially in farming areas mainly because of gaseous emission and water pollution. Among all the pollutants emitted from manure waste, ammonia is of greatest concern as it could contribute to formation of aerosols in the air and could hardly be controlled by traditional disposal methods like landfill or composting. On the other hand, manure waste is also a renewable source for energy production. In this work, an environmental friendly animal waste disposal process with combined ammonia recovery and energy production was proposed and investigated both experimentally and economically. Lab-scale feasibility study results showed that 70% of ammonia in the manure waste could be converted to struvite as fertilizer, while solid manure waste was successfully gasified in a 10 kW downdraft fixed-bed gasifier producing syngas with the higher heating value of 4.9 MJ/(N m 3 ). Based on experimental results, economic study for the system was carried out using a cost-benefit analysis to investigate the financial feasibility based on a Singapore case study. In addition, for comparison, schemes of gasification without ammonia removal and incineration were also studied for manure waste disposal. The results showed that the proposed gasification-based manure waste treatment process integrated with ammonia recovery was most financially viable.